SANKSI ADMINISTRASI TERHADAP PELANGGARAN PERIZINAN PERUSAHAAN MINYAK DAN GAS BUMI - Mushawirya, Rustian (Faculty of Law, University of Palembang, 2018)
The objective of the research is to analyze and explain the administrative sanctions against violations of licensing of oil and gas companies. The research method used normative juridical method. Research result: Oil and gas business activities are always required to support the sustainability of national development in order to increase the prosperity and prosperity of the people of Earth always above. To realize the enactment of Law No. 22 Year 2001 on Oil and Natural Gas (UU-Migas). This law as the legal basis for the steps to reform and restructure business activities in the oil and gas fields conflict of authority in the application of administrative sanctions between the local government and the government in order to become the implementation of oil and gas cooperation contract in Indonesia. The local government is based on the actions of theoretical economies. SKK Migas said it is not central authority (centralization). This study will first examine whether local governments can impose administrative sanctions on companies holding oil and gas cooperation contracts that violate the provisions of location permits What is the legal action of SKK Migas against administrative sanctions imposed by the local government on companies holding contracts of oil and gas cooperation Firstly, legislation and official documents so as to obtain legal documentation on the authority of the administrative sanction of the company holding the oil and gas cooperation contract holder violating the location permit provisions. Second, to review the legal action of SKK Migas against the administrative sanctions imposed by the local government on companies holding contracts for oil and gas cooperation